Prognostic value of temporal patterns of global longitudinal strain in patients with chronic heart failure - Abou Kamar, Sabrina; Aga, Yaar S.; de Bakker, Marie; van den Berg, Victor J.; Strachinaru, Mihai; Bowen, Dan; Frowijn, René; Akkerhuis, K. Martijn; Brugts, Jasper; Manintveld, Olivier; Umans, Victor; Geleijnse, Marcel L.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background We investigated whether repeatedly measured global longitudinal strain (GLS) has incremental prognostic value over repeatedly measured left ventricular ejection fraction (LVEF) and N-terminal pro B-type natriuretic peptide (NT-proBNP), and a single “baseline” GLS value, in chronic heart failure (HF) patients. Methods In this prospective observational study, echocardiography was performed in 173 clinically stable chronic HF patients every six months during follow up. During a median follow-up of 2.7 years, a median of 3 (25th–75th percentile:2–4) echocardiograms were obtained per patient. The endpoint was a composite of HF hospitalization, left ventricular assist device, heart transplantation, cardiovascular death. We compared hazard ratios (HRs) for the endpoint from Cox models (used to analyze the first available GLS measurements) with HRs from joint models (which links repeated measurements to the time-to-event data). Results Mean age was 58 ± 11 years, 76% were men, 81% were in New York Heart Association functional class I/II, and all had LVEF < 50% (mean ± SD: 27 ± 9%). The endpoint was reached by 53 patients. GLS was persistently decreased over time in patients with the endpoint. However, temporal GLS trajectories did not further diverge in patients with versus without the endpoint and remained stable during follow-up. Both single measurements and temporal trajectories of GLS were significantly associated with the endpoint [HR per SD change (95%CI): 2.15(1.34–3.46), 3.54 (2.01–6.20)]. In a multivariable model, repeatedly measured GLS maintained its prognostic value while repeatedly measured LVEF did not [HR per SD change (95%CI): GLS:4.38 (1.49–14.70), LVEF:1.14 (0.41–3.23)]. The association disappeared when correcting for repeatedly measured NT-proBNP. Conclusion Temporal evolution of GLS was associated with adverse events, independent of LVEF but not independent of NT-proBNP. Since GLS showed decreased but stable values in patients with adverse prognosis, single measurements of GLS provide sufficient information for determining prognosis in clinical practice compared to repeated measurements, and temporal GLS patterns do not add prognostic information to NT-proBNP.